The influence of job rotation in the job satisfaction of nurses in a surgical service = - Dinis, LIC (2018)
Theoretical framework: Job satisfaction is associated with better performance, leading to an optimisation of healthcare. Objectives: To understand the influence of job rotation between units of the same service in the nurses’ job satisfaction. Methodology: Observational, analytic, cross-sectional and quantitative study using a questionnaire and subsequent bivariate descriptive statistical analysis. Results: Statistically significant results were found in the variables related to the nurse’s service, satisfaction with the number of shifts, pace of work, and technicality. The nurses who were very dissatisfied with the job rotation were professionally satisfied. On the other hand, the nurses who were very satisfied with the job rotation were somewhat professionally satisfied. Although no association was found between satisfaction and rotation, nurses informally expressed their dissatisfaction. Thus, a qualitative or mixed study should have been developed. Conclusion: The engagement of nurses in the decision-making process, particularly regarding the rotation system, should be continuously valued as it allows nurses to expand their field of action and achieve better results. Enquadramento: A satisfação profissional está associada a melhores resultados no trabalho permitindo uma otimização dos cuidados de saúde. Objectivos: Compreender a influência da rotação no trabalho, entre secções do mesmo serviço, na satisfação profissional dos enfermeiros. Metodologia: Estudo quantitativo, observacional, analítico e transversal, com recurso a 1 questionário e posterior análise estatística descritiva e bivariada dos dados. Resultados: Resultados referentes à proveniência do enfermeiro, satisfação com o número de turnos, ritmo de trabalho e tecnicidade, foram estatisticamente significativos. Os enfermeiros muito insatisfeitos com a rotação estavam profissionalmente satisfeitos. Por outro lado, os enfermeiros muito satisfeitos com a rotação estavam profissionalmente bastante satisfeitos. Não se verificou associação entre satisfação e rotação, mas denotou-se uma verbalização informal de insatisfação por parte dos enfermeiros, tornando-se ideal a realização de um estudo qualitativo ou misto. Conclusão: A participação dos enfermeiros no processo de tomada de decisão, nomeadamente quanto ao sistema de rotação, deve ser continuamente valorizada, uma vez que permite ao trabalhador expandir o seu campo de ação e atingir melhores resultados.